What's next? how professionals are refusing retirement - Roche-Tarry, Dona (Palgrave Macmillan, 2011)
Studies the steps taken by a group of professionals from the Boomer generation as they move from a linear career path into an uncharted stage somewhere between middle age and old age, a continued professional life and traditional retirement. What is next for those professionals who do not want to take a back seat at retirement age?